In vivo interaction of bilirubin with the cells of the immune system in mice: an ultrastructural electronmicroscopic study - Vĕtvicka, V; Rossmann, P; Bilej, M; Miler, I; Knobloch, E; Síma, P (Cell biology international reports, 1989)
Morphological evidence revealed the presence of round-shaped particles after application of bilirubin. The possibility of polymerization of bilirubin-albumin complexes is discussed.
Keywords: Peritoneal Cavity; myši; makrofágy; Macrophages; bilirubin; Animals; mužské pohlaví; Microscopy, Electron; ženské pohlaví; Mice, Inbred BALB C; zvířata; Mice; Female; peritoneální dutina; Bilirubin; myši inbrední BALB C; Male; elektronová mikroskopie